Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Sepeda Motor Merek Honda di Kota Pontianak - Januarti, Fida; Ahmadi, Ahmadi; Rosadi, Rosadi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Motorcycles are one of the vehicles that are mostly used by the people of Pontianak city, therefore it requires companies to have a good marketing strategy, one of which is using a marketing mix. This study used a quantitative method with hypothesis testing using partial tests and simultaneous tests. The results of the partial hypothesis test stated that the product variable had a significant value of 0.302 while the price, place and promotion variables had an effect with a significantly smaller value than t table, namely 0.05. Simultaneously test the hypothesis with a Fcount value of 64.759. It can be concluded that the hypothesis with the results of the t test states that the product variable has no positive and significant impact on purchasing decisions while the price, place and promotion variables have an effect. the results of the f test state that the independent variables tested simultaneously have a positive and significant effect on the dependent variable.